1997
DOI: 10.1002/(sici)1096-9861(19970120)377:3<423::aid-cne9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Compound synapses within the GABAergic innervation of the auditory inner hair cells in the adolescent mouse

Abstract: Ultrastructural investigation of the gamma-aminobutyric acid (GABA) component of the inner spiral bundle in adolescent mice revealed a pathway of glutamic acid decarboxylase (GAD)-positive and -negative fibers and vesiculated endings that contact inner hair cells and their afferents through a complex of axosomatic and axodendritic synapses. Ultrastructural details were investigated by using conventional electron microscopy. Several synaptic arrangements were observed: Main axosomatic synapses form between vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 112 publications
1
22
0
Order By: Relevance
“…Sobkowicz and colleagues (1994; 1997; 2002) also identified axosomatic efferent terminals in the cochlear apex and mid-turn of developing mice of the outbred ICR strain. As in aging C57 mice, efferents in young ICR mice occasionally formed synapses with two IHCs, termed “inter-receptor synapses.” GABAergic signaling is known to produce neurotrophic effects (Lauder, 1993) and has been suggested to play a role in the maintenance of hair cells and auditory nerve fibers (Maison et al, 2006; Ruel et al, 2001).…”
Section: Discussionmentioning
confidence: 86%
“…Sobkowicz and colleagues (1994; 1997; 2002) also identified axosomatic efferent terminals in the cochlear apex and mid-turn of developing mice of the outbred ICR strain. As in aging C57 mice, efferents in young ICR mice occasionally formed synapses with two IHCs, termed “inter-receptor synapses.” GABAergic signaling is known to produce neurotrophic effects (Lauder, 1993) and has been suggested to play a role in the maintenance of hair cells and auditory nerve fibers (Maison et al, 2006; Ruel et al, 2001).…”
Section: Discussionmentioning
confidence: 86%
“…8D) showing the existence of synaptic contacts. However, synapse ribbons, which are included in characteristics for afferent synaptic contacts between IHCs and SGN dendrites (Sobkowicz, 1992; Sobkowicz et al, 1997), were not observed in the base of IHCs attaching to ESC‐derived nerve endings.…”
Section: Resultsmentioning
confidence: 99%
“…This represents the first evidence of synapse formation between ESC‐derived neurons and IHCs. In normal cochleae of mature mice, afferent synapse contacts at the base of IHCs are characterized by the presence of synaptic ribbons and by a postsynaptic membrane density on the dendrite (Sobkowicz, 1992; Sobkowicz et al, 1997). However, in TEM analysis, no synaptic ribbons were found in the base of IHCs adjacent to ESC‐derived nerve endings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOC innervation is biased towards the IHC modiolar side; there, low-SR fibers are innervated by twice as many LOC terminals as high-SR fibers [22]. In addition, a small number of LOC neurons synapse directly on IHCs [21, 40, 41]. LOC efferents contain a variety of neurotransmitters, including dopamine (DA), dynorphin (dyn), enkepalin (enk), γ-aminobutyric acid (GABA), acetylcholine (ACh), and calcitonin-gene-related peptide (CGRP) [for reviews, see 1, 7, 12, 16, 18, 34].…”
mentioning
confidence: 99%